A Solution to a Single Molecular Experiment Problem (Communications in Computational Physics, 2009)
Recently Hari Shroff and his collaborators [Nano Letters 5 (2005)] developeda nanoscopic force sensor, but the force which they measured in their single molecularexperiment was much lower than the theoretical critical value. In order to fix thisproblem, we investigate the micromechanics of dsDNA based on the worm-like chainmodel and flexible hinge model by using Monte Carlo algorithm. The simulation resultsnot only address Hari Shroff's experiment difficulty reasonably, but also providestrong support for flexible hinge mechanism put forward recently by Yan and Marko[Phys. Rev. Lett. 93 (2004)].